Effects of Collagen Hydrolysate From Large Hybrid Sturgeon on Mitigating Ultraviolet B-Induced Photodamage - Chen, Bei; Yu, Lei; Wu, Jingna; Qiao, Kun; Cui, Lulu; Qu, Haidong; Su, Yongchang; Cai, Shuilin; Liu, Zhiyu; Wang, Qin (Frontiers in Bioengineering and Biotechnology, 2022)
Ultraviolet B (UVB) radiation leads to the excessive accumulation of reactive oxygen species (ROS), which subsequently promote inflammation, degradation of the extracellular matrix, and photoaging in skin. Thus antioxidant activity is particularly important when screening for active substances to prevent or repair photodamage. Marine fish-derived bioactive peptides have become a trend in cosmetics and functional food industries owing to their potential dermatological benefits. In this study, 1-diphenyl- 2-pycryl-hydrazyl (DPPH) scavenging activity was selected to optimize the hydrolysis conditions of sturgeon skin collagen peptides with antioxidant activity. The optimal hydrolysis conditions for sturgeon skin collagen hydrolysate (SSCH) were determined by response surface methodology, which comprised an enzyme dosage of flavorzyme at 6068.4 U/g, temperature of 35.5 ºC, pH of 7, and hydrolysis time of 6 h. SSCH showed good radical-scavenging capacities with a DPPH scavenging efficiency of 95%. Then, the effect of low-molecular-weight SSCH fraction (SSCH-L) on UVB irradiation-induced photodamage was evaluated in mouse fibroblast L929 cells and zebrafish. SSCH-L reduced intracellular ROS levels and the malondialdehyde content, thereby alleviating the oxidative damage caused by UVB radiation. Moreover SSCH-L inhibited the mRNA expression of genes encoding the pro-inflammatory cytokines IL-1β, IL-6, TNF-α, and Cox-2. SSCH-L treatment further increased the collagen Ⅰα1 content and had a significant inhibitory effect on matrix metalloproteinase expression. The phosphorylation level of JNK and the expression of c-Jun protein were significantly reduced by SSCH-L. Additionally, SSCH-L increased the tail fin area at 0.125 and 0.25 mg/mL in a zebrafish UVB radiation model, which highlighted the potential of SSCH to repair UVB-irradiated zebrafish skin damage. Peptide sequences of SSCH-L were identified by liquid chromatography-tandem mass spectrometry. Based on the 3D-QSAR modeling prediction, six total peptides were selected to test the UVB-protective activity. Among these peptides, DPFRHY showed good UVB-repair activity, ROS-scavenging activity, DNA damage-protective activity and apoptosis inhibition activity. These results suggested that DPFRHY has potential applications as a natural anti-photodamage material in cosmetic and functional food industries.